2021
DOI: 10.3389/fphar.2021.673263
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics-Based Chronoefficacy of Semen Strychni and Tripterygium Glycoside Tablet Against Rheumatoid Arthritis

Abstract: Rheumatoid arthritis is a systemic autoimmune disease characterized by synovial inflammation and bone destruction. Identifying drugs with time-varying efficacy and toxicity, and elucidating the mechanisms would help to improve treatment efficacy and reduce adverse effects. Here, we aimed to determine the chronoefficacy of semen strychni (SS) and tripterygium glycoside tablet (TGT) against rheumatoid arthritis in mice, and to investigate a potential role of circadian pharmacokinetics in generating chronoefficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Clinical practice indicates that SS has an apparent effect on MG. Studies demonstrated that treatment with SS decreased the production of proinflammatory cytokines and inhibited the TLR-4/NF-kB signaling pathway in EAMG rats [ 9 ]. Although many studies have focused on the anti-inflammatory and neurotransmitter-regulating effects of SS [ 16 , 17 ], the underlying mechanisms have not been systematically uncovered. Our team desired to further investigate the mechanism of SS in the treatment of MG.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practice indicates that SS has an apparent effect on MG. Studies demonstrated that treatment with SS decreased the production of proinflammatory cytokines and inhibited the TLR-4/NF-kB signaling pathway in EAMG rats [ 9 ]. Although many studies have focused on the anti-inflammatory and neurotransmitter-regulating effects of SS [ 16 , 17 ], the underlying mechanisms have not been systematically uncovered. Our team desired to further investigate the mechanism of SS in the treatment of MG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on TGT pharmacokinetics have mainly focused on healthy animals, or animals with rheumatoid arthritis. Of note, the severity of rheumatoid arthritis was positively correlated with plasma exposure to WFG and WFR in rats after TGT administration ( Su et al, 2015a ; Lin et al, 2021 ; Zhao et al, 2021 ). Thus, it is rational to investigate the influence of NS on the key TGT components, as NS is another clinical indication for TGT.…”
Section: Discussionmentioning
confidence: 92%
“…According to the Chinese Pharmacopoeia, [ 17 ] NV has the effect of promoting pain, dispersing nodules and, reducing swelling, and can be used to treat rheumatic paralysis and numbness and paralysis. Current studies point out that NV can excite spinal cord reflex functions, stimulate the medullary respiratory and vasomotor centers, and increase the excitability of the sensory center of the cerebral cortex, [ 7 , 18 ] but the underlying mechanism is unclear. Notably, Strychnine and brucine are the main components and the main toxic components of NV, which must be strictly controlled in dosage.…”
Section: Discussionmentioning
confidence: 99%
“…center of the cerebral cortex, [7,18] but the underlying mechanism is unclear. Notably, Strychnine and brucine are the main components and the main toxic components of NV, which must be strictly controlled in dosage.…”
Section: Mol/herb Id Component Name Degreementioning
confidence: 99%